2021
DOI: 10.1016/j.redox.2021.102126
|View full text |Cite
|
Sign up to set email alerts
|

Chemoproteomic profiling reveals cellular targets of nitro-fatty acids

Abstract: Nitro-fatty acids are a class of endogenous electrophilic lipid mediators with anti-inflammatory and cytoprotective effects in a wide range of inflammatory and fibrotic disease models. While these beneficial biological effects of nitro-fatty acids are mainly attributed to their ability to form covalent adducts with proteins, only a small number of proteins are known to be nitro-alkylated and the scope of protein nitro-alkylation remains undetermined. Here we describe the synthesis and application of a clickabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…The complexity involved in detecting a PTM as nitroalkylation must be highlighted. To date, this modification had only been identified and characterized in in vitro studies [61]. This makes the present research work the first study to detect the in vivo NO 2 -OA-mediated nitroalkylation.…”
Section: Discussionmentioning
confidence: 91%
“…The complexity involved in detecting a PTM as nitroalkylation must be highlighted. To date, this modification had only been identified and characterized in in vitro studies [61]. This makes the present research work the first study to detect the in vivo NO 2 -OA-mediated nitroalkylation.…”
Section: Discussionmentioning
confidence: 91%
“…In 2021, Zhang et al reported the synthesis of 9-nitroeicos-9-en-19-ynoic acid (99), a derivative of 9-NO 2 -OA, where a terminal triple bond exists (Scheme 25) [119]. Compound 99 may serve as a tool of detecting in general which mammalian proteins can form covalent adducts with the electrophilic center of this NO 2 -FA.…”
Section: Step-by-step Synthesis Of No2-fasmentioning
confidence: 99%
“…Moreover, the clickable nature of DA-CB may be leveraged to trace the cellular fate of the modified fatty acid or any derived synthetic intermediate. 20…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition to its efficacy, DA-CB is an intriguing lead compound because a strained cyclic alkene is present. This feature enables selective addressing of DA-CB or any derived biosynthetic intermediate via a “click” reaction, providing a handle with which to decipher the location of the fatty acid analogue or derived conjugates within the mycobacterial cell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation